Sustainability in the entrepreneurial ecosystem operating mechanisms and enterprise growth - Tsai, Sang-Bing, 1973-; Du, Xiaomin, 1985-; Xin, Chunlin, 1971- (Business Science Reference (an imprint of IGI Global), 2020)
"This book is a collection of innovative research that systematically explores the operation mechanism of sustainable entrepreneurship ecosystem from macro and micro aspects so as to provide value for promoting economic vitality and regional economic development"--